Relevance of tumor boards for the inclusion of patients in oncological clinical trials - Hendrik Dapper; Maurice Dantes; Peter Herschbach; Hana Algül; Volker Heinemann (Journal of Cancer Research and Clinical Oncology)
Abstract Introduction Major national and international oncological societies generally recommend treating a significant proportion of oncological patients in clinical trials to improve therapy strategies for cancer patients. At cancer centers, the recommendation about the appropriate therapy for the individual tumor patient is usually made in interdisciplinary case discussions in multidisciplinary tumor boards (MDT). In this study, we examined the impact of MDTs for the inclusion of patients in therapy trials. Methodology A prospective, explorative study of the Comprehensive Cancer Center Munich (CCCM) was conducted at both university hospitals in 2019. In the first phase, various MDTs’ case discussions about oncological situations and their decisions regarding possible therapy trials were recorded in a structured manner. In the second phase, the actual inclusion rates of patients in therapy trials and reasons for non-inclusion were examined. Finally, the data of the respective university hospitals were anonymized, pooled and analyzed. Results A total of 1797 case discussions were reviewed. Therapy recommendations were made in 1527 case presentations. 38 (2.5%) of 1527 patients were already included in a therapy trial at the time of case presentation. The MDTs recommended inclusion of an additional 107 cases (7%), for a therapy trial. Of these patients, 41 were finally enrolled in a therapy trial which resulted in a total recruitment rate of 5.2%. Despite MDTs’ recommendations, 66 patients were not included in a therapy trial. The main reason for non-inclusion was insufficient inclusion or existing exclusion criteria (n = 18, 28%). In 48% of all cases (n = 31), the reason for non-inclusion could not be determined. Conclusion The potential of MDTs as an instrument for the inclusion of patients in therapy trials is high. To increase the enrollment of patients in oncological therapy trials, structural measures such as the central use of trial administration and MTB software in addition to standardized tumor board discussions must be established to ensure a seamless flow of information about actual recruiting trials and the current status of trial participation of patients.